CIPP Model Analysis for Evaluation of the Stunting Reduction Acceleration Program Policy: A Case Study of Hunuth/Durian Patah Village, Ambon City - Harmiati Mewal; Ima Mayasari (Ranah Research : Journal of Multidisciplinary Research and Development, 2026)
This study evaluates the acceleration of stunting reduction in Hunuth Village, Ambon City, using the CIPP model (Context, Input, Process, Product) to identify success factors. A qualitative case study method was employed, utilizing in-depth interviews, field observations, and document analysis. Results indicate a dramatic decline in stunting prevalence from 21.80% in 2021 to 1.9% in 2024, significantly surpassing the 14% national target. This achievement is driven by visionary village leadership and the strategic prioritization of Village Funds for health and sanitation infrastructure. Implementation successfully integrated specific interventions, such as nutrition monitoring, with sensitive interventions like the Healthy Kitchen to Overcome Stunting program and improved waste management. High community participation and empowered health cadres were essential to this progress. While challenges regarding data recording accuracy and consistent household parenting practices remain, Hunuth Village serves as a premier model for institutionalizing stunting mitigation through effective village-level governance and cross-sectoral collaboration.